Multimodel and multiconstituent scenario construction for future water quality - Bouwman, A. F.; Bärlund, I.; Beusen, A. H. W.; Flörke, M.; Gramberger, M.; Rivera Cardona, J.; Podgorski, J.; van den Roovaart, J.; Grizzetti, B.; Janssen, A. B. G.; Kumar, R.; Langan, Simon; et al. (American Chemical Society, 2024)
Freshwater pollution is, together with climate change, one of today’s most severe and pervasive threats to the global environment. Comprehensive and spatially explicit scenarios covering a wide range of constituents for freshwater quality are currently scarce. In this Global Perspective paper, we propose a novel model-based approach for five water quality constituents relevant for human and ecosystem health (nitrogen, biochemical oxygen demand, anthropogenic chemicals, fecal coliform, and arsenic). To project the driving forces and consequences for emissions and impacts, a set of common data based on the same assumptions was prepared and used in different large-scale water quality models including all relevant demographic, socioeconomic, and cultural changes, as well as threshold concentrations to determine the risk for human and ecosystem health. The analysis portrays the strong links among water quality, socio-economic development, and lifestyle. Internal consistency of assumptions and input data is a prerequisite for constructing comparable scenarios using different models to support targeted policy development.